Implementing an EDRMS: case study of a nuclear power company in China. Issue 1 (January 2018) - Wang, Xiangnyu
Abstract : This paper seeks to understand Electronic Document and Records Management Systems (EDRMS) and develop a holistic process model for managing electronic records in a nuclear power station EDRMS. It takes a case study approach, and its findings are: (1) process management implementation needs to be driven from the top; (2) the records and archives management function belongs to a single department and records should be described in standardized ways by record managers and records creators; (3) archivists should shift their emphasis from preserving the records to integrating all the business processes of the institution with records processes, and that this should be done before designing an EDRMS; (4) training users is very important; (5) records managers should pay attention to taxonomies and think about the user's perspective. The case study contributes to the understanding of the relationship between EDRMS and total process management theory.